2018
DOI: 10.5937/fmet1804595r
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of glass-carbon/epoxy hybrid composites subjected to low velocity impact test

Abstract: Hybrid composites with multiple reinforcements of high strength are very popular for many engineering applications, especially for impact resistance. In the present work, we report the development of the glasscarbon/epoxy hybrid composites using hand lay technique and investigate its low velocity impact response. Low velocity impact tests were performed on the hybrid composites of two different thicknesses 2 mm and 4 mm to study the impact resistance of hybrid composites with respect to impact energy and impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…[ 18,19 ] Many years ago, McCrum et al [ 20 ] provided two reasons for the continuous and unended expansion for the utilization of polymer resins in the engineering application due to their higher performance (resistance from chemical and corrosion, toughness, and lightness) and versatility comprised with the shaping process [ 19,21 ] at which the raw resin matrix and various other additives are converted into essential hardware products. This process is presently proved in terms of their applications in packaging, automobile, [ 22 ] aerospace, [ 23 ] defense, [ 24 ] sports, marine, control of vibration, [ 25 ] anticorrosion, [ 26 ] many thermomechanical applications, [ 27 ] and piezoelectric sensor. [ 28 ] Polymeric composites reinforced with nanoparticles are presently achieving higher interest as they promise engineering materials with varying characteristics improvement courtesy of the various nanofillers reinforced in the polymer resin matrix.…”
Section: Introductionmentioning
confidence: 99%
“…[ 18,19 ] Many years ago, McCrum et al [ 20 ] provided two reasons for the continuous and unended expansion for the utilization of polymer resins in the engineering application due to their higher performance (resistance from chemical and corrosion, toughness, and lightness) and versatility comprised with the shaping process [ 19,21 ] at which the raw resin matrix and various other additives are converted into essential hardware products. This process is presently proved in terms of their applications in packaging, automobile, [ 22 ] aerospace, [ 23 ] defense, [ 24 ] sports, marine, control of vibration, [ 25 ] anticorrosion, [ 26 ] many thermomechanical applications, [ 27 ] and piezoelectric sensor. [ 28 ] Polymeric composites reinforced with nanoparticles are presently achieving higher interest as they promise engineering materials with varying characteristics improvement courtesy of the various nanofillers reinforced in the polymer resin matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Glass -carbon/epoxy hybrid composites were tested against the low velocity impact. This study concluded that defect in these composites has significant effect on energy absorption during the impact (Venkategowda et al, 2018). For fatigue application of the composite material, Kevlar-49 was chosen as the fibre material whereas cork powder and nanoclays were used to improve the impact resistance and tensile strength of these laminates (Kaliraj et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…While research on traditional carbon and glass fiber reinforced polymer (CFRP and GFRP) composites [1][2][3][4][5] and sandwich composite materials [6][7][8][9][10] is still ongoing, fiber metal laminates (FMLs) have been introduced as a new composite family in recent years in order to meet the different mechanical property demands of engineers. Fiber metal laminates are composite materials consisting of alternating layers of metal and composite bonded together using epoxy adhesive [11].…”
Section: Introductionmentioning
confidence: 99%